Patient and provider perspectives of the implementation of remote consultations for community-dwelling people with mental health conditions: A systematic mixed studies review. (December 2022) - Galvin, Emer; Desselle, Shane; Gavin, Blánaid; Quigley, Etain; Flear, Mark; Kilbride, Ken; McNicholas, Fiona; Cullinan, Shane; Hayden, John
Abstract: Remote, or tele-, consultations became a necessary form of mental healthcare provision during the COVID-19 pandemic. As the prevalence of mental health problems rises, they may have a role in future mental health services. We aimed to review the literature on patient and provider perspectives on factors influencing the implementation of remote consultations for community-dwelling people with mental health conditions. We searched five electronic databases (PubMed, EMBASE, Web of Science, CINAHL, and PsycINFO) for empirical research up to July 13th, 2022. Only studies of synchronous, interactive remote consultations conducted via video, phone, or live-messaging between patients and providers were included. Two reviewers independently assessed the quality of included studies using the Mixed Methods Appraisal Tool. We integrated qualitative and quantitative data from 39 studies into a single mixed-methods synthesis. We mapped reported factors to the domains of the Consolidated Framework for Implementation Research (CFIR). Acceptability was generally high among participants, despite concerns about the quality of care and the perceived impeded therapeutic relationship. A prominent facilitator was the increased accessibility and convenience of remote consultations, while lack of appropriate infrastructure and low patient comfort and competence were among the most prevalent barriers. This review highlights the importance of patient preferences and provider buy-in to the future of remote consultations.